PENGEMBANGAN BAHAN AJAR STATISTIKA DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING UNTUK MEMFASILITASI KEMAMPUAN KONEKSI MATEMATIS SISWA - Putri, Amanda Handya; Armis, Armis; Syofni, Syofni (ALGORITMA: Journal of Mathematics Education, 2023)
AbstractThis research aims to develop instructional materials for teaching statistics using a contextual teaching and learning strategy. The goal is to enhance the mathematical connection abilities of eighth-grade junior high school students. The materials are designed to meet the criteria of validity and practicality. The present study involves the development of a 4-D model, encompassing the stages of Define, Design, Develop, and Disseminate. The validation process was carried out by involving three experts. Data pertaining to the feasibility of the teaching materials were acquired through testing conducted on eighth-grade students in a junior high school. The present study examines the validation outcomes of teaching materials, which were categorised as highly valid. Based on the findings of the readability assessment, it was determined that the average score for the "easy to understand" category was 86.97%. In addition, the practicality test meets the "very practical" category. These findings indicate that the use of a contextual approach in statistics material effectively improves students' mathematical connection abilities. This technique proves to be legitimate, easily comprehensible, and particularly beneficial for promoting the development of mathematical connections among eighth-grade junior high school students. AbstrakPenelitian ini bertujuan dalam pengembangan bahan ajar untuk pengajaran statistika menggunakan strategi pengajaran dan pembelajaran kontekstual untuk meningkatkan kemampuan koneksi matematis siswa SMP kelas delapan. Materi dirancang untuk memenuhi kriteria validitas dan kepraktisan. Penelitian ini melibatkan pengembangan model 4-D, yang mencakup tahapan Define, Design, Develop, dan Disseminate. Proses validasi dilakukan dengan melibatkan tiga orang ahli. Data mengenai kelayakan bahan ajar diperoleh melalui pengujian yang dilakukan pada siswa kelas delapan di sekolah menengah pertama. Penelitian ini mengkaji hasil validasi bahan ajar yang dikategorikan sangat valid. Berdasarkan hasil penilaian keterbacaan yang dilakukan, diperoleh bahwa skor rata-rata untuk kategori "mudah dipahami" adalah 86,97%. Selain itu, uji kepraktisan memenuhi kategori "sangat praktis". Temuan ini menunjukkan bahwa penggunaan pendekatan kontekstual dalam materi statistika efektif meningkatkan kemampuan koneksi matematis siswa. Bahan ajar ini terbukti valid, mudah dipahami, dan sangat bermanfaat untuk mendorong pengembangan koneksi matematika di kalangan siswa kelas delapan SMP.